Electron kinetics of yttrium iron garnet after swift heavy ion impact - Rymzhanov, R.A.; Volkov, A.E.; Ibrayeva, A.D. (KU Pabl, 2022)
The TREKIS Monte-Carlo model was applied to study the temporal electronic kinetics of yttrium iron garnet after a swift heavy ion impact. Cross sections of incident particles interaction with the target were determined within complex dielectric function-dynamic structure factor formalism. We found two modes of the spatial propagation of electronic excitation: fast delta-electrons form a front of the excitation while electrons produced due to decay of plasmons generated in a track form the second front slowly following behind the first one. Analysis of mechanisms of target lattice heating pointed to an important contribution of the potential energy released due to recombination of valence holes generated in an ion track. An increase of the excess lattice energy due to elastic scatterings of electrons and holes described with Mott cross-sections is minor. In contrast, complex dielectric function formalism demonstrates the significant contribution of these processes to the heating of the lattice.
Keywords: swift heavy ion track; electron excitations; complex dielectric function; ion energy loss; Monte Carlo simulations